2020
DOI: 10.3892/mmr.2020.11294
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity patterns in diabetic patients with vitreous hemorrhage using amplitude of low‑frequency fluctuation: A resting‑state fMRI study

Abstract: The aim of the present study was to assess the local character of spontaneous brain activity in type-2 diabetic patients with vitreous hemorrhage (VH) and its relationship with clinical features via the amplitude of low-frequency fluctuations (alFF) method. a total of 31 subjects (15 females and 16 males) with type-2 diabetic VH and 31 normal controls (ncs) with similar characteristics (sex, age and educational level) were recruited in the present study. all subjects underwent resting-state functional magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…However, there were two outliers at the longest illness duration in the regression plot (Figure 3). When excluding the two datasets (Shi et al, 2020;Zhang Y. Q. et al, 2020), no significant association was found between the illness duration and regional activity in patients with T2DM. The mean age, percentage of males, education, onset age, HbA 1c %, BMI, and MMSE scores were not linearly associated with regional function alteration in patients with T2DM.…”
Section: Metaregression Analysismentioning
confidence: 83%
See 4 more Smart Citations
“…However, there were two outliers at the longest illness duration in the regression plot (Figure 3). When excluding the two datasets (Shi et al, 2020;Zhang Y. Q. et al, 2020), no significant association was found between the illness duration and regional activity in patients with T2DM. The mean age, percentage of males, education, onset age, HbA 1c %, BMI, and MMSE scores were not linearly associated with regional function alteration in patients with T2DM.…”
Section: Metaregression Analysismentioning
confidence: 83%
“…A total of 47 articles were identified through the systematic literature search, and Figure 1 shows the details of study selection process. We finally included 16 studies (19 T2DM datasets and 15 healthy controls datasets) in the final meta-analysis (Xia et al, 2013;Cui et al, 2014;Wang et al, 2014Wang et al, , 2019Zhou et al, 2014;Liu et al, 2016;Peng et al, 2016;Wang Y. F. et al, 2017;Wang Z. L. et al, 2017;Liao et al, 2019;Liu Y. et al, 2020;Qi et al, 2020;Shi et al, 2020;Xiong et al, 2020;Zhang Y. Q. et al, 2020). In two studies of ReHo, the analysis was performed in two different T2DM subgroups (Peng et al, 2016;Xiong et al, 2020), and in another study, the analysis was performed with ALFF and ReHo (Cui et al, 2014).…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations